Early Earthquake Disaster Response Management: The BSMI Humanitarian Aid Experience in Turkey - Supartono, Basuki; Muftisany, Hafidz; Rudi, Muhamad (Indonesian Red Crescent Humanitarian Journal, 2023)
On February 6, 2023, the regions of Turkey and Syria were struck by a devastating earthquake during the winter season, resulting in numerous casualties, injuries, displacement, and infrastructure damage. In response, the Turkish president appealed for international assistance, prompting the Indonesian Red Crescent to deploy a humanitarian aid team. The methods employed encompassed three stages: preparation, implementation, and evaluation. The implementation phase involved coordination, collaboration, and the distribution of humanitarian aid. The distribution of essential items such as ready-to-eat food, winter clothing, and medicine took place in Hatay Province and Kahramanmaras, Turkey. Effective coordination was established with the governments of Indonesia and Turkey, alongside collaboration with humanitarian agencies and Turkish medical organizations. Additionally, plans for the subsequent deployment of the medical team were reviewed. All activities were successfully executed and received positive feedback.  The Indonesian Red Crescent successfully provided crucial assistance in response to the earthquake disaster in Turkey. The efforts encompassed various aspects, including aid distribution, coordination with relevant authorities, collaboration with partner organizations, and future planning. The outcomes achieved were noteworthy and yielded a positive impact.